EFFECT OF DIETARY SUPPLEMENTATION OF BORIC ACID ON THE SERUM BIOCHEMICAL, TIBIA MORPHOMETRY AND MINERALIZATION OF JAPANESE QUAIL (Coturnix coturnix japonica) - V. Sai Chaitanya; D. Narendra Nath; K. Nagaraja Kumari; D. Srinivas Kumar; L. Murali (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was carried out to evaluate the effect of dietary supplementation of boric acid on serum biochemical, tibia morphometry and mineralization of Japanese quail fed diets supplemented with boric acid at different levels of 0, 15, 30, 45 and 60 ppm were prepared in a 5 x 3 design. A total of 150 day-old Japanese quail chicks were individually weighed and allotted randomly into five treatment groups with three replicates containing ten birds each, the birds were fed with experimental diets for a period of 5 weeks. At the end of the 5th week, two birds per replicate an average of six birds per treatment were slaughtered. Blood and tibia were collected accordingly. Serum calcium level significantly (p